Baobab shell powder as a bio-filler in HDPE composites: mechanical, and physical properties - Daniel S. Sudi; Haruna Wante; Ndubuisi Mbada; Isah Baba; Bamidele Boluwatife; Solomon Adeleke (Recent Advances in Natural Sciences)
This study develops and characterizes high-density polyethylene (HDPE) composites reinforced with 0–20 wt% baobab shell powder (BSP) as a sustainable bio-filler. Composites were fabricated via compression molding and assessed for mechanical, physical, and chemical properties. XRF analysis revealed high metal oxide content in BSP—K2O (29.32%), MgO (16.27%), CaO (12.42%), Al2O3 (12.12%), and SiO2 (11.73%)—indicating multifunctional potential. FTIR confirmed lignocellulosic functional groups (O–H, C–H, C=O, C–O). Tensile strength peaked at 10.996 N/mm2 (20 wt%, +6.14% vs. neat HDPE); yield strength peaked at 26.35 N/mm2 (15 wt%), suggesting improved matrix interaction. Flexural strength dropped to 2.24 N/mm2 at 10 wt% but stabilized thereafter; elongation at break fell from 37.74% to 7.87%, indicating increased rigidity. Impact energy dropped from 4.0 J to 1.63 J, while hardness and density rose from 11.36 to 28.66 N/m2 and 0.87 to 0.93 g/cm3, respectively. Water absorption remained low until day 6, then rose sharply to ~20% (20 wt%) by day 8 due to interfacial degradation. Composites with ≤10 wt% BSP showed better moisture resistance. The results demonstrated that BSP enhances stiffness, hardness, and tensile strength but reduces ductility and impact resistance, making it suitable for non-structural applications in automotive, packaging, and sustainable construction.